2021
DOI: 10.3389/fmolb.2021.687576
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Downregulation of miRNA-1827 and Its Prognostic Significance by Targeting SPTBN2 and BCL2L1 in Ovarian Cancer

Abstract: Background: Previous studies demonstrated that miRNA-1827 could repress various cancers on proliferation, angiogenesis, and metastasis. However, little attention has been paid to its role in ovarian cancer as a novel biomarker or intervention target, especially its clinical significance and underlying regulatory network.Methods: A meta-analysis of six microarrays was adopted here to determine the expression trend of miRNA-1827, and was further validated by gene expression profile data and cellular experiments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…What’s more, SPTBN2 was associated with poor prognosis in patients with colorectal cancer and was highly expressed in patients with distant metastasis, lymph node metastasis, and clinical advanced colorectal cancer, with statistically significant differences [ 8 ]. In recent studies, it has been confirmed that the mRNA and protein levels of SPTBN2 were upregulated in ovarian cancer, and which was involved in a variety of biological processes associated with tumorigenesis and was highly associated with poor prognosis of ovarian cancer [ 9 ]. In our study, we found SPTBN2 was significantly upregulated in human UCEC for the first time, and the high expression of SPTBN2 was related to poor prognosis, suggesting that SPTBN2 can be served as a powerful predictor of UCEC prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What’s more, SPTBN2 was associated with poor prognosis in patients with colorectal cancer and was highly expressed in patients with distant metastasis, lymph node metastasis, and clinical advanced colorectal cancer, with statistically significant differences [ 8 ]. In recent studies, it has been confirmed that the mRNA and protein levels of SPTBN2 were upregulated in ovarian cancer, and which was involved in a variety of biological processes associated with tumorigenesis and was highly associated with poor prognosis of ovarian cancer [ 9 ]. In our study, we found SPTBN2 was significantly upregulated in human UCEC for the first time, and the high expression of SPTBN2 was related to poor prognosis, suggesting that SPTBN2 can be served as a powerful predictor of UCEC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a protein-coding gene, the protein products of SPTBN2 belong to the Spectrin family. Studies have shown that SPTBN2 is up-regulated in MPNST [ 7 ], colorectal cancer [ 8 ], and ovarian cancer [ 9 ],which was involved in a variety of biological processes related to tumorigenesis. SPTBN2 has been identified as one of the marker genes for the pathogenesis of cancer and plays an important role in the pathogenesis of cancer, which is of great significance for understanding the pathogenesis and early diagnosis of cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence has extensively proven that SPTBN2 plays a vital role in the diagnosis of cholangiocarcinoma. For example, by using a bioinformatics approach, Feng et al demonstrated that SPTBN2 is highly associated with poor prognosis in ovarian cancer [ 25 ]. Zhang et al and Yue et al reported that SPTBN2 may play a vital role in the progression of colorectal cancer [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This gene mutation can lead to spinocerebellar ataxia ( Yıldız et al, 2017 ). In ovarian cancer, the upregulation of SPTBN2 has been associated with poor prognosis ( Feng et al, 2021 ). TIMP1, tissue inhibitor matrix metalloproteinase-1, belongs to the tissue inhibitor of metalloproteinases family.…”
Section: Discussionmentioning
confidence: 99%